1997
DOI: 10.1074/jbc.272.48.30122
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Structure and Function of the Fourth Member of p38 Group Mitogen-activated Protein Kinases, p38δ

Abstract: We have cloned and characterized a new member of the p38 group of mitogen-activated protein kinases here termed p38␦. Sequence comparisons revealed that p38␦ is approximately 60% identical to the other three p38 isoforms but only 40 -45% to the other mitogen-activated protein kinase family members. It contains the TGY dual phosphorylation site present in all p38 group members and is activated by a group of extracellular stimuli including cytokines and environmental stresses that also activate the other three k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
375
0
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 461 publications
(386 citation statements)
references
References 45 publications
5
375
0
6
Order By: Relevance
“…Although the other three p38 group members have been cloned for quite some time now, little is known regarding their activation. Despite research that has shown that all four p38 group members display similar activation profiles [5,8,24,25], differences have been observed in the kinetics and level of activation of these isoforms. Furthermore, the activation of p38 isoforms can be specifically controlled through different regulators and coactivated by various combinations of upstream regulators [24,26].…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the other three p38 group members have been cloned for quite some time now, little is known regarding their activation. Despite research that has shown that all four p38 group members display similar activation profiles [5,8,24,25], differences have been observed in the kinetics and level of activation of these isoforms. Furthermore, the activation of p38 isoforms can be specifically controlled through different regulators and coactivated by various combinations of upstream regulators [24,26].…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 92%
“…p38 cDNA was also cloned as a molecule that binds puridinyl imidazole derivatives which are known to inhibit biosynthesis of inflammatory cytokines such as interleukin-1 (IL-1) and tumor-necrosis factor (TNF) in LPS stimulated monocytes [4]. To date, four splice variants of the p38 family have been identified: p38α, p38β [5], p38γ (ERK6, SAPK3) [6,7], and p38δ (SAPK4) [8,9]. Of these, p38 and p38β are ubiquitously expressed while p38γ and p38δ are differentially expressed depending on tissue type.…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…JNKs are activated by two distinct MAPKKs, MKK4/SEK1 (Sanchez et al, 1994;Derijard et al, 1995), and MKK7 Yao et al, 1997;Wu et al, 1997;Tournier et al, 1997;Holland et al, 1997), in the JNK signaling unit. The p38 subgroup is composed of four genes including p38a, p38b, p38g and p38d (Han et al, 1994;Lee et al, 1994;Jiang et al, 1997;Stein et al, 1997;Goedert et al, 1997;Wang et al 1997). The p38s are also activated by at least two MAPKKs, MKK3 and MKK6 (Stein et al, 1996;Moriguchi et al, 1996).…”
Section: Upstream Kinases In the Jnk And P38 Modulesmentioning
confidence: 99%
“…p38 MAPK is in turn phosphorylated and hence activated by two upstream MAP kinase kinases (MAPKKs, or MKKs), MKK3 (Derijard et al, 1995) and MKK6 . Of the four p38 isoforms (α, β, γ and δ), only p38α and p38β isoforms are substantially expressed in heart Li et al, 1996;Jiang et al, 1997). Selective activation of different p38 isoforms by distinct MKKs has also been observed; MKK6, which is 80 % homologous to the isoform MKK3, can activate all four p38 isoforms, whereas MKK3 preferentially activates only p38α, p38γ, and p38δ Keesler et al, 1998).…”
Section: Introductionmentioning
confidence: 99%